2013
DOI: 10.1021/jp403352u
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Investigation of the Adsorption of Ethanol–Water Mixture on the Pt(111) Surface

Abstract: Steam reforming of ethanol–water mixture is a promising renewable route to obtain hydrogen; however, our atomistic understanding of the interaction of ethanol–water mixture with transition-metal surfaces is far from satisfactory. In this work, we report a density functional theory investigation of the adsorption properties of the ethanol–water mixture on the Pt(111) surface employing semilocal exchange-correlation functional within nonlocal van der Waals corrections. From our calculations and analysis, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
33
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 64 publications
11
33
0
7
Order By: Relevance
“…As found in previous DFT studies with vdW corrections, 22,27,28 the D3 vdW correction increases the adsorption energy. For example, the enhancement factor that is dened as the ratio between the PBE+D3 and PBE adsorption energies ranges from 2.25 to 2.80 for glycerol on the low-coordinated Pt 6 sites.…”
Section: Adsorption Energysupporting
confidence: 79%
See 3 more Smart Citations
“…As found in previous DFT studies with vdW corrections, 22,27,28 the D3 vdW correction increases the adsorption energy. For example, the enhancement factor that is dened as the ratio between the PBE+D3 and PBE adsorption energies ranges from 2.25 to 2.80 for glycerol on the low-coordinated Pt 6 sites.…”
Section: Adsorption Energysupporting
confidence: 79%
“…These results are supported by our previous ndings for alcohol molecules on close-packed TM surfaces. 22,27,28 As expected, the adsorbed structures in which glycerol binds on the terrace sites, e.g., structures F and G, are similar to the adsorbed structure with glycerol bound on the clean Pt(100) surface, that is, d O-Pt is 2.31 A and 2.33Å for structure F and the structure with glycerol bound on the clean Pt(100) surface, respectively.…”
Section: Glycerol Adsorbed Structuressupporting
confidence: 71%
See 2 more Smart Citations
“…Depending on the nature of the metal, the ethoxide intermediate formed during ethanol adsorption, is either converted to an adsorbed oxametallacycle (favored over Ru or Rh catalysts) or to adsorbed acetaldehyde (favored over Pt or Pd catalysts) [49][50][51], with both conformations suggesting coordination to multiple surface atoms. On the other hand it has been reported that ethanol adsorption geometry is strongly modified over hydrated or hydroxylated surfaces [48,52,53]. In the former case, ethanol does not interact directly with metallic surface, but with the pre-adsorbed water molecule, resulting in an acetaldehyde molecule, H-bonded with the water molecule and with the C O bond being almost parallel to the surface.…”
Section: Ethanol Adsorption On the Pt Surfacementioning
confidence: 99%